Hubungan kepuasan kerja dengan work engagement pada karyawan PT. KI Daerah Istimewa Yogyakarta - Saputra, Dwi; Bantam, Dian Juliarti (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
The company has components in supporting productivity, human resources are an important component to develop the company. Employees having work engagement can provide inherent energy and attention and give their best to their work. One of the factors of work engagement is job resources related to job satisfaction, job satisfaction has a positive relationship with work engagement. Employees show a positive level of feelings for the work done. The purpose of this study is to determine the relationship between job satisfaction and work engagement in employees of PT. KI Special Region of Yogyakarta. Respondents from this study were company employees with male and female genders and already had the status of permanent employees. This study uses a quantitative approach with data collection tools using the UWES-9 scale (Utrecht Work Engagement Scale) developed by Bakker and Schaufeli, while the second scale uses JSS (Job Satisfaction Survey) developed by Spector. The participating subjects numbered 50 employees. Data analysis using pearson's product moment. The results of the study showed a positive relationship between job satisfaction and work engagement in employees with r = 0.715 and a significance value of p = 0.00 (p<0.05), so it can be said that the hypothesis in this study was accepted.